2010
DOI: 10.1111/j.1420-9101.2010.02024.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional adaptation of spiriferide brachiopod morphology

Abstract: It has been suggested that spiriferide morphologies have evolved to adapt to a variety of environmental conditions. Through a computational fluid dynamics approach, we examined how the spiriferide original form was optimized for a lotic condition, specifically addressing the functionalization of the Devonian spiriferide brachiopod Paraspirifer bownockeri to generate passive feeding flows. The results using four models, each of which differed in the development of the spiriferide shell depression, i.e. sulcus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 30 publications
0
54
0
Order By: Relevance
“…The CFD simulation methods used here have been fully described in previous reports by our group (Shiino et al 2009(Shiino et al , 2012Shiino & Kuwazuru 2010, 2011a. The methodology is briefly described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFD simulation methods used here have been fully described in previous reports by our group (Shiino et al 2009(Shiino et al , 2012Shiino & Kuwazuru 2010, 2011a. The methodology is briefly described below.…”
Section: Methodsmentioning
confidence: 99%
“…The simulation was performed using the commercial computational fluid dynamics code SCRYU/Tetra 9.0 (Software Cradle Co., Ltd., Tokyo, Japan), which employs the finite-volume method (e.g., Adkins & Yan 2006, Shiino et al 2009). To implement a three-dimensional model of Hypodicranotus for analysis in the CFD simulation, we constructed a polycarbonate exoskeletal replica using the vacuum-forming method (Shiino et al 2009, Shiino 2010) and obtained sequential cross-sectional images of the replica using an SMX-225CT microfocus X-ray CT system (Shimadzu Corporation, Tokyo, Japan). Subsequently, the volumetric data were translated into surface morphological data in • C -hypostome (MCZ-100987).…”
Section: Computational Fluid Dynamics (Cfd) Simulationsmentioning
confidence: 99%
“…It has been suggested that the shell of Paraspirifer passively generated inflow and outflow for feeding and respiration (Shiino et al, 2009;Shiino, 2010;Shiino and Kuwazuru, 2010b). To generate passive flow, the sulcus must generate a pressure difference between the sulcus and lateral gapes, with the higher pressure at the sulcus (Shiino et al, 2009).…”
Section: Passive Feeding Flow Of Paraspirifermentioning
confidence: 98%
“…Almost all animal forms are apparently formulated in a way that makes it possible to perform requisite physiological and ecological tasks. In light of the fact that the expression of a function is nonlinear with a morphological change (Koehl, 1996;Shiino and Kuwazuru, 2010b), it is necessary to quantitatively estimate how differences in morphological characteristics affect biological performance and how morphological plasticity allows for the maintenance of that performance.…”
Section: Introductionmentioning
confidence: 99%
“…Spiriferinids, which were one of the most thrived brachiopod groups and showed no indications of colour [36], became extinct soon after the diversification of the macropredators even though they possessed certain morphologies that are considered to be exquisite adaptations for feeding system [37][38][39][40][41]. On the other hand, terebratulids did not become extinct but began to diversify and persisted to the modern era [42].…”
Section: One Likely Possibility For the Evolutionary Arms Race Betweementioning
confidence: 99%